Analisis Unsur Religius Pada Novel “Dalam Mihrab Cinta” Karya Habiburrahman El - Shirazy - Maftuhah (Jurnal Pendidikan Islam, 2018)
Abstract: This study aims to describe the religious element contained in the novel “Dalam Mihrab Cinta”. This study used a qualitative description of the research. Qualitative research is used to obtain a picture empirical about religiosity in the novel “Dalam Mihra b Cinta” Habiburrahman El - Shirazy work. This study uses a structural approach and pragmatic approach, this analysis can be seen from the aspect of religion (aqidah, sharia, morals, and jurisprudence) and researchers trying to find the values contained in t he novel “Dalam Mihrab Cinta”. Results from this study are able to analyze the elements of religious values (aqidah,sharia, and morals) and aimed to introduce the science of jurisprudence that stirs the soul trough a love story that is so unique and intere sting to the reader in the novel “Dalam Mihrab Cinta” Habiburrahman El - Shirazy work.